PELATIHAN PEMBUATAN BUSINESS PLAN DAN MENGEMBANGKAN KEMAMPUAN SERTA KETRAMPILAN DALAM BISNIS DI ERA DIGITAL DI SMA NEGERI 2 BAYANG KABUPATEN PESISIR SELATAN - Malik, David; Suandi, Edi; Yulihardi, Yulihardi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This community service program aims to enhance business skills among students at SMA Negeri 2 Bayang, Pesisir Selatan Regency, through training in business plan development and the utilization of digital technology. In today’s digital era, understanding business planning and the ability to leverage digital platforms for promotion and business expansion have become increasingly essential, especially for the younger generation. The program comprises several stages, including theoretical sessions on business planning, practical workshops on business plan creation, and digital marketing training. Students are trained to develop a basic business plan covering market analysis, marketing strategy, and cost planning. Additionally, they are introduced to utilizing social media and other digital platforms for promotional purposes.The outcomes of this program indicate improved student comprehension of business planning and digital marketing skills. With this training, students are expected to apply these skills in navigating the business world in the future and to be more competitive in an increasingly digital business environment. The program also provides opportunities for students to develop innovative business ideas relevant to local market needs.